DISASTER-RESILIENT HOSPITALS: THE NOAH'S ARK - Mani, Geetha; Danasekaran, Raja; Annadurai, Kalaivani (YCAB Publisher & IAKMI SULTRA, 2016)
Health services are important lifelines of a community any time and this role is more pronounced during times of disasters. Evidence from various parts of the world presents examples of disaster-induced damage to hospitals and failure of health services at times of need. The impact of disasters-induced damage to health care is three-dimensional: health, social and economic. Damage to health care facilities apart from delaying and complicating relief measures also compromise the achievement of planned national and global health and related goals. The indirect and long-term costs of damage to health sector are greater than direct and immediate costs, compounding the disastrous consequences on the economy. The increasing invasion of nature spaces, climate change and urbanisation are bound to aggravate more natural hazards in future. So a resilient health care system is an immediate necessity for all global states. This paper discusses the international and national endeavours towards a resilient health-care system and analyses the strategies to promote safe hospitals in future.